Effects of Sex on the Relationship Between Apolipoprotein E Gene and Serum Lipid Profiles in Alzheimer’s Disease - Fu, Jiajia; Huang, Yan; Bao, Ting; Ou, Ruwei; Wei, Qianqian; Chen, Yongping; Yang, Jing; Chen, Xueping; Shang, Huifang (Frontiers in Aging Neuroscience, 2022)
Background Sex is an important factor in studying the relationship between the APOE gene, lipid profiles, and AD. However, few studies have focused on the effect of sex on lipids in AD and normal controls with different APOE genes. Materials and Methods A total of 549 participants, including 298 AD patients and 251 body mass index (BMI)-matched healthy controls (HCs), were enrolled. Lipid profiles and APOE genes in both AD patients and HCs were determined. Results (1) TC and LDL were higher in AD patients than in HCs, only in APOEε4 carrying populations, but not in non-carrying populations. (2) TC and LDL were higher in APOEε4 allele carriers than in non-carriers, only in AD populations, but not in HCs. (3) The TC of APOEε2 carriers was lower than that of non-carriers in the male AD population, but not in the female AD population, female HCs, and male HCs. (4) The increased LDL level may increase the risk of AD in female people carrying APOEε4. Conclusion The TC and LDL levels of APOEε4 carriers were higher than those of non-carriers, and the effect was more significant in the female AD population. The TC levels in APOEε2 carriers were lower than those in non-carriers, which was more significant in the male AD population.